VARIATIONS IN PREVALANCE AND INTENSITY OF WORK RELATED MUSCULOSKELETAL DISORDERS IN DIFFERENT DEPARTMENTS AMONG DENTAL PROFESSIONALS - MOHAMED FAISAL.C.K; LAWRENCE MATHIAS (International Journal of Pharma and Bio Sciences, 2014)
Work related musculoskeletal disorders (WMSDs) are becoming crucial and require the identification and modification of risk factors. Since the dentists work for around eight hours a day in the static awkward postures may lead to musculoskeletal discomfort. The objectives of this study are to evaluate the WMSD in dental professionals and compare the intensity and prevalence of musculo-skeletal dysfunction in various departments of dental specialties. 306 dentists with the mean age of 31.7, working experience of 7.2 years and 41.34 working hours in a week were considered for this study and evaluated with the self administered Nordic musculo skeletal evaluation chart and Postural Discomfort chart. The results shows that, dental professionals are at high risk to get WMSDs such as pain, ache, numbness and discomfort at anatomical areas like neck, low back, shoulder, wrist and hand because of their routine working posture. Orthodontists were found to be having a higher risk of neck, shoulder and wrist and hand, musculo skeletal symptoms whereas prosthodontists were having a higher ratio of musculo skeletal symptoms at Low back region. Majority of the musculoskeletal symptoms are seen one or more times in a week in dental professionals and female dentists are more prone to have musculo-skeletal disorders compared to male dentists.